Small Ideas for Saving Big Health Care Dollars - Liu, Jodi L. (RAND Corporation, 2014)
A focused review of RAND Health research identified small ideas that could save the U.S. health care system $13 to $22 billion per year if successfully implemented. They include changing payment policy for emergency transport and greater use of $4 generic drugs. Small ideas do not require systemic change; thus, they may be both more feasible to operationalize and less likely to encounter stiff political and organizational resistance.